OPTIMAL STRATEGIES FOR DENGUE CONTROL: WOLBACHIA-INFECTED MOSQUITOES DEPLOYMENT, PUBLIC HEALTH EDUCATION, AND VACCINATION - Toni Bakhtiar; Jaharuddin Jaharuddin; Farida Hanum (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2026)
Wolbachia-infected mosquitoes present a promising method for dengue control by inhibiting viral replication, reducing mosquito reproductive capacity, and shortening the lifespan of Aedes aegypti mosquitoes. This study introduces a novel optimal control model that uniquely integrates two distinct release strategies for Wolbachia-infected mosquitoes—constant and proportional rates. While prior research has explored Wolbachia deployment, our model is the first to directly compare and contrast these two rate types within the same framework to assess their differential impact on dengue transmission dynamics. This provides a more comprehensive understanding of effective release protocols, addressing a critical gap in the literature regarding optimal and adaptive Wolbachia deployment. Based on model simulations for North Kembangan Village, Jakarta, we find that a single-control strategy using Wolbachia mosquito release alone can reduce dengue cases by up to 15%. However, a multiple-control strategy that combines Wolbachia releases with public health education and vaccination is the most effective approach, achieving a substantial reduction of up to 58%. In a cost-effectiveness analysis, the study reveals that the Wolbachia-only strategy (proportional release) is the most cost-effective in terms of cost per infection averted. In terms of release dynamics, the study reveals that a constant release rate provides long-term benefits by establishing a stable Wolbachia-infected mosquito population, whereas a proportional release rate is more effective for achieving a rapid, short-term reduction in dengue cases.